Investigation of the in vivo genotoxic effects of a titanium dioxide nanomaterial in LacZ plasmid-based transgenic mice - Louro, Henriqueta (2014)
Titanium dioxide nanomaterials (TiO2) are increasingly used in a diversity of products, including cosmetics, pharmaceuticals, food and inks, which contrasts with the existing uncertainties in respect to their risks for human and environment health. Previous studies on the genotoxicity of TiO2 reported discrepant findings, both in cellular and organismal systems. In a recent work, we showed that some nanosized TiO2 were able to induce a significant increase in the frequency of micronucleated human lymphocytes, whereas for anatase TiO2 (NM-102, JRC repository), this effect was observed with a single significant concentration, providing inconclusive evidence. To further investigate the genotoxic potential of NM-102, the LacZ plasmid-based transgenic mouse model was used allowing an integrated analysis of multiple genotoxicity endpoints at a whole-organism level. Following two administrations of 0, 10 or 15 mg/kg of NM-102 by intravenous route within a 24h period, the micronucleus frequency was determined in peripheral blood reticulocytes whereas DNA strand breaks (comet assay) and gene mutations were quantified in spleen and liver cells 28 days after exposure. Histopathological analyses were concomitantly performed in liver tissues, using both light and transmission electron microscopy (TEM). The results did not show any significant genotoxic effects after exposure to the TiO2 NM under the experimental conditions used, but a moderate inflammatory response was observed in liver. In addition, TEM evidenced the presence of TiO2 in liver cells. The overall integration of the data strengthens the weight of evidence of an absence of TiO2 genotoxicity in vivo, although the possibility of a secondary genotoxic effect driven by an inflammatory response within a longer time window or at higher doses cannot be excluded and should be further investigated.